Aircraft Technology - Cemal Kuşhan, Melih (IntechOpen, 2018)
It is well known that improvements in space and aviation are the leader of today's technology, and the aircraft is the most important product of aviation. Because of this fact, the books on aircraft are always at the center of interest. In most cases, technologies designed for the aerospace industry are rapidly extending into other areas. For example, although composite materials are developed for the aerospace industry, these materials are not often used in aircraft. However, composite materials are utilized significantly in many different sectors, such as automotive, marine and civil engineering. And materials science in aviation, reliability and efficiency in aircraft technology have a major importance in aircraft design.